2020
DOI: 10.3390/cells9071627
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type Targeted NF-kappaB Inhibition for the Treatment of Inflammatory Diseases

Abstract: Deregulated NF-k activation is not only involved in cancer but also contributes to the pathogenesis of chronic inflammatory diseases like rheumatoid arthritis (RA) and multiple sclerosis (MS). Ideally, therapeutic NF-KappaB inhibition should only take place in those cell types that are involved in disease pathogenesis to maintain physiological cell functions in all other cells. In contrast, unselective NF-kappaB inhibition in all cells results in multiple adverse effects, a major hindrance in drug deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 183 publications
(255 reference statements)
0
48
0
Order By: Relevance
“…It has been found that NF-κB is conserved across different phyla, and, in mammalian and avian species, it consists of a group of five related proteins (subunits) that are capable of binding to DNA: p50 (a 50 kDa protein also known as NF-κB1), p52 (known as NF-κB2), p65 (also known as RelA), c-Rel, and RelB. In fact, p65, RelB, and c-Rel are characterized by a C-terminal transcription activation domain (TAD) that participates in the positive regulation of gene expression [ 50 ]. Interestingly, the other NF-κB family members, NF-κB1 and NF-κB2, were shown to be synthetized as larger precursor proteins (p105 and p100) with subsequent proteolytic processing to p50 and p52 [ 47 ].…”
Section: Transcription Factor Nuclear Factor Kappa Bmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been found that NF-κB is conserved across different phyla, and, in mammalian and avian species, it consists of a group of five related proteins (subunits) that are capable of binding to DNA: p50 (a 50 kDa protein also known as NF-κB1), p52 (known as NF-κB2), p65 (also known as RelA), c-Rel, and RelB. In fact, p65, RelB, and c-Rel are characterized by a C-terminal transcription activation domain (TAD) that participates in the positive regulation of gene expression [ 50 ]. Interestingly, the other NF-κB family members, NF-κB1 and NF-κB2, were shown to be synthetized as larger precursor proteins (p105 and p100) with subsequent proteolytic processing to p50 and p52 [ 47 ].…”
Section: Transcription Factor Nuclear Factor Kappa Bmentioning
confidence: 99%
“…Therefore, it is believed that, in order to inhibit further transcription and restore the original latent state of NF-κB signaling, newly synthesized IκBα can enter the nucleus, remove NF-κB from DNA, and export the complex back to the cytoplasm [ 49 ]. Interestingly, the canonical NF-κB pathway is considered to be antiapoptotic, while the noncanonical pathway is proapoptotic [ 50 ].…”
Section: Transcription Factor Nuclear Factor Kappa Bmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in the expression of proinflammatory genes, the activation of the inflammasome and loss of vascular integrity in endothelial cells (8)(9)(10)(11). Unselective pharmacological inhibition of NF-κB, across cell types, results in multiple adverse effects; a major hindrance in drug development (12). The nuclear translocation of NF-κB dimers is dependent upon a dynein/dynactin motorimmunophilin complex, indicating that immunophilins can fine tune the signaling cascade (13,14).…”
Section: Introductionmentioning
confidence: 99%